2016
DOI: 10.1021/acs.joc.6b01190
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Scale Membrane Reactor for the Generation of Anhydrous Diazomethane

Abstract: A configurationally simple and robust semibatch apparatus for the in situ on-demand generation of anhydrous solutions of diazomethane (CH2N2) avoiding distillation methods is presented. Diazomethane is produced by base-mediated decomposition of commercially available Diazald within a semipermeable Teflon AF-2400 tubing and subsequently selectively separated from the tubing into a solvent- and substrate-filled flask (tube-in-flask reactor). Reactions with CH2N2 can therefore be performed directly in the flask w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 55 publications
1
49
0
Order By: Relevance
“…Whilst remaining impermeable to the liquid phase, Teflon AF-2400 allows gasses to rapidly permeate through its amorphous microporous structure. [21,22] Initially used in synthetic applications with ozone, [23] these devices have since been used with a diverse array of gasses including hydrogen, [24,25] ammonia, [26][27][28] oxygen, [29][30][31][32][33][34] ethene, [35][36][37] carbon monoxide, [38,39] syngas [40] and diazomethane [41,42]. Jensen and co-workers have also used this material to remove an ethene byproduct in a continuous flow application.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst remaining impermeable to the liquid phase, Teflon AF-2400 allows gasses to rapidly permeate through its amorphous microporous structure. [21,22] Initially used in synthetic applications with ozone, [23] these devices have since been used with a diverse array of gasses including hydrogen, [24,25] ammonia, [26][27][28] oxygen, [29][30][31][32][33][34] ethene, [35][36][37] carbon monoxide, [38,39] syngas [40] and diazomethane [41,42]. Jensen and co-workers have also used this material to remove an ethene byproduct in a continuous flow application.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Ther esulting products 4i-k were obtained in 68-85 %y ield (entries 8-10). [2][3][4][5][6] Notably,only halogen-lithium exchanges of o-nitroarenes [2,6] and an alkenyl iodide containing an aliphatic azide [6] at À100 8 8Cu nder batch conditions are known, as well as several flow methods for ester-, ketone-, and nitrocontaining arenes that involve applying ultrafast micromixing and residence times down to 0.0015 s. [8] Again, we found that in the absence of am etal salt, 4-iodophenyl azide [17] (5a) decomposes completely when performing the reaction in flow. [16] To further demonstrate the broad applicability of in situ trapping exchange reactions in flow,w ei nvestigated the compatibility of these exchanges with aryl halides bearing challenging functional groups such as ester, ketone,nitro,and heterocumulene groups,f or example,a na zide or isothiocyanate.…”
mentioning
confidence: 85%
“…[16] To further demonstrate the broad applicability of in situ trapping exchange reactions in flow,w ei nvestigated the compatibility of these exchanges with aryl halides bearing challenging functional groups such as ester, ketone,nitro,and heterocumulene groups,f or example,a na zide or isothiocyanate. [2][3][4][5][6] Notably,only halogen-lithium exchanges of o-nitroarenes [2,6] and an alkenyl iodide containing an aliphatic azide [6] at À100 8 8Cu nder batch conditions are known, as well as several flow methods for ester-, ketone-, and nitrocontaining arenes that involve applying ultrafast micromixing and residence times down to 0.0015 s. [8] Again, we found that in the absence of am etal salt, 4-iodophenyl azide [17] (5a) decomposes completely when performing the reaction in flow. However,s creening of various in situ trapping exchange conditions,f or example,a ddition of soluble metal salts,f low rate,a nd temperature, [13] led to the desired allylated phenyl azide 7a in 72 %yield of isolated product (Scheme 3).…”
mentioning
confidence: 99%
“…[4,5] Thesynthesis of TMSCHN 2 by the diazo-transfer reaction of TMSCH 2 MgCl with diphenyl phosphoryl azide has been largely adopted because of the facile scalability of the process. [8] For example,d iazomethane has been generated in flow from commercially available Diazald [9] and N-methyl-N-nitrosourea (MNU;S cheme 1). [8] For example,d iazomethane has been generated in flow from commercially available Diazald [9] and N-methyl-N-nitrosourea (MNU;S cheme 1).…”
Section: Batch and Continuous-flowone-pot Processes Using Amine Diazomentioning
confidence: 99%
“…[6] Despite these advantages,afew drawbacks remain, including long reaction times (> 20 h), as well as the tedious distillation of ether from TMSCHN 2 .C ontinuousflow processes [7] have been developed to safely prepare diazo reagents and mitigate some of these challenges. [8] For example,d iazomethane has been generated in flow from commercially available Diazald [9] and N-methyl-N-nitrosourea (MNU;S cheme 1). [10] Thec ontinuous flow synthesis of diazoesters and aryldiazomethanes from hydrazones has also been described.…”
Section: Batch and Continuous-flowone-pot Processes Using Amine Diazomentioning
confidence: 99%